2017
DOI: 10.1371/journal.pone.0171469
|View full text |Cite
|
Sign up to set email alerts
|

Description of recovery method used for curdlan produced by Agrobacterium sp. IFO 13140 and its relation to the morphology and physicochemical and technological properties of the polysaccharide

Abstract: Curdlan is a linear polysaccharide considered a dietary fiber and with gelation properties. This study evaluated the structure, morphology and the physicochemical and technological properties of curdlan produced by Agrobacterium sp. IFO 13140 recovered by pre-gelation and precipitation methods. Commercial curdlan submitted or otherwise to the pre-gelation process was also evaluated. The data obtained from structural analysis revealed a similarity between the curdlan produced by Agrobacterium sp. IFO 13140 (rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
0
16
1
Order By: Relevance
“…However, the addition of higher levels of curdlan increased syneresis up to 40%. Although previous studies found that the addition of curdlan decreased the syneresis of yoghurt (Mangolim, et al, 2017;, however the concentration they used (1.5%) was higher than that used in this study and the yoghurt formulation in this study did not include fat. Further previous studies (Chapter 5) found that the selected pure curdlan started to form gel at concentration > 1.0%.…”
Section: Syneresiscontrasting
confidence: 60%
See 3 more Smart Citations
“…However, the addition of higher levels of curdlan increased syneresis up to 40%. Although previous studies found that the addition of curdlan decreased the syneresis of yoghurt (Mangolim, et al, 2017;, however the concentration they used (1.5%) was higher than that used in this study and the yoghurt formulation in this study did not include fat. Further previous studies (Chapter 5) found that the selected pure curdlan started to form gel at concentration > 1.0%.…”
Section: Syneresiscontrasting
confidence: 60%
“…This suggests that addition of curdlan endows the yoghurt to have a better ability to maintain the structure, hindering rearrangements among the casein network during storage and reducing the expulsion of whey. Yoghurts contains curdlan were produced by Ortiz Martinez et al (2016) and Mangolim et al (2017), and compared with the yoghurt without curdlan they also found the curdlan-contained yoghurts got an obvious reduction in syneresis. The authors attributed this improvement to the interactions among curdlan molecules, either between curdlan itself or with the dairy proteins.…”
Section: Application Of Curdlan In Yoghurtmentioning
confidence: 98%
See 2 more Smart Citations
“…Xanthan, gellan, and curdlan are the three exopolysaccharides, which has been approved as food additives by the food and drug administration 2 . Curdlan clumps as a strong gel totally in the thermal suspension and never return to aqueous state again 3 .…”
Section: Article Can Be Accessed Online Onmentioning
confidence: 99%